Housing Markets in Uruguay: Determinants of Housing Demand and its Interaction with Public Policies - Natalia Garabato; Magdalena Ramada-Sarasola (Inter-American Development Bank (IDB), 2011)
This paper analyzes the determinants of housing demand for Uruguay and the extent to which housing policies have an impact on their target population. The paper first analyzes the determinants of housing demand, following an approach based on Rosens (1974) two-step procedure consisting of fitting a hedonic price regression in 34 different geographical units (or markets) to estimate a housing demand function. The determinants of formality and ownership choices were examined using a multinomial logit framework. Determinants of these choices include both household demographic attributes and access to and use of public housing programs and other social programs. Policy recommendations are offered on the basis of the finding that a price and income-inelastic formal housing market greatly contrasts with a rather price and income-elastic informal housing market.
Keywords: G21; I38; O54; R21; R28; R38; 330